2019
DOI: 10.3390/met9091012
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure, Mechanical Properties, and Corrosion Resistance of UNS S32707 Hyper-Duplex Stainless Steel Processed by Selective Laser Melting

Abstract: UNS S32707 hyper-duplex stainless steel (HDSS) parts with complex shapes for ocean engineering were prepared by selective laser melting (SLM) process. In the process of SLM, the balance between austenite and ferrite was undermined due to the high melting temperature and rapid cooling rate, resulting in poor ductility and toughness. The solution annealing was carried out with various temperatures (1050-1200 • C) for one hour at a time. The evolution of microstructures, mechanical properties, and corrosion resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Shang et al [123] observed, using EBSD, that secondary phases, such as sigma, were precipitated after SLM processing on 2707 HDSS. However, after the same processing and additional solution annealing treatments, at different temperatures, it gave place to a balanced ferrite-austenite microstructure.…”
Section: Selective Laser Melting Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al [123] observed, using EBSD, that secondary phases, such as sigma, were precipitated after SLM processing on 2707 HDSS. However, after the same processing and additional solution annealing treatments, at different temperatures, it gave place to a balanced ferrite-austenite microstructure.…”
Section: Selective Laser Melting Processesmentioning
confidence: 99%
“…Table 4 shows a summary of different duplex stainless steel grades processed by WAAM and SLM processes, the post-AM heat treatments applied, and the pitting corrosion potential. Balanced ratio ferrite-austenite; higher pitting corrosion resistance after solution annealing [123] In conclusion, additive manufacturing processes are a promising alternative method to fabricate duplex stainless steels, especially when complex and irregular shapes are required in addition to the density of the materials, in comparison to the conventional techniques. However, high cooling rates and control during the processes are of extreme importance in order to avoid the formation of deleterious secondary phases that can affect mechanical and corrosion resistance properties.…”
Section: Selective Laser Melting Processesmentioning
confidence: 99%
“…Shang et al studied the corrosion behavior of the UNS S32707 hyper-duplex SS with solution annealing from 1050 to 1200 • C [48]. The electrochemical experiments showed that the samples with a solution treatment at 1100 • C for 1 h had the best pitting resistance.…”
Section: Corrosion Behaviors Of the Slm Miscellaneous Type Ss Corrosimentioning
confidence: 99%
“…The pitting initiation and the hysteresis of the cyclic polarization curves in the studied potential range were observed in the SLM as-built samples, but they were not observed after the heat treatment. Shang et al studied the corrosion behavior of the UNS S32707 hyper-duplex SS with solution annealing from 1050 to 1200 °C [48]. The electrochemical experiments showed that the samples with a solution treatment at 1100 °C for 1 h had the best pitting resistance.…”
Section: Corrosion Behaviors Of the Slm Miscellaneous Type Ss Corrosimentioning
confidence: 99%
“…In recent years, the development of additive manufacturing technology has introduced a new metal-forming process with extremely fast cooling rates [14][15][16][17][18][19][20][21]. The one-time Materials 2023, 16, 7125 2 of 11 forming method reduces spending on molds and allows for the manufacturing of more complex structural components, while avoiding issues like σ phase precipitation and grain coarsening during casting cooling [19,[22][23][24][25][26][27][28]. The characteristics of additive manufacturing effectively address the issues of casting formation and the diversification of product forms in duplex stainless steel.…”
Section: Introductionmentioning
confidence: 99%